csrB Gene Duplication Drives the Evolution of Redundant Regulatory Pathways Controlling Expression of the Major Toxic Secreted Metalloproteases in Vibrio tasmaniensis LGP32 - An Ngoc Nguyen (American Society for Microbiology, 2018)
ABSTRACT CsrBs are bacterial highly conserved and multiple-copy noncoding small RNAs (sRNAs) that play major roles in cell physiology and virulence. In the Vibrio genus, they are known to be regulated by the two-component system VarS/VarA. They modulate the well-characterized quorum sensing pathway controlling virulence and luminescence in Vibrio cholerae and Vibrio harveyi, respectively. Remarkably, Vibrio tasmaniensis LGP32, an oyster pathogen that belongs to the Splendidus clade, was found to have four copies of csrB, named csrB1-4, compared to two to three copies in other Vibrio species. Here, we show that the extra csrB4 copy results from a csrB3 gene duplication, a characteristic of the Splendidus clade. Interestingly, csrB genes are regulated in different ways in V. tasmaniensis, with csrB1 expression being independent of the VarS/VarA system. We found that a complex regulatory network involving CsrBs, quorum sensing, and the stationary-phase sigma factor σS redundantly but differentially controls the production of two secreted metalloproteases, Vsm and PrtV, the former being a major determinant of the V. tasmaniensis extracellular product toxicity. In particular, we identified a novel VarS/VarA-dependent but CsrB-independent pathway that controls positively both Vsm production and PrtV production as well as rpoS expression. Altogether, our data show that a csrB gene duplication event in V. tasmaniensis supported the evolution of the regulatory network controlling the expression of major toxic secreted metalloproteases, thereby increasing redundancy and enabling the integration of additional input signals. IMPORTANCE The conserved CsrB sRNAs are an example of sibling sRNAs, i.e., sRNAs which are present in multiple copies in genomes. This report illustrates how new copies arise through gene duplication events and highlights two evolutionary advantages of having such multiple copies: differential regulation of the multiple copies allows integration of different input signals into the regulatory network of which they are parts, and the high redundancy that they provide confers a strong robustness to the system.